Ergative Markers in Taleshi Dialect and its Dependency on Past Tense and Aspect - Abdullah ezzat doust; Mojtaba Monshizadeh; Hayat Ameri (̒Ilm-i Zabān, 2022)
This present research studies ergativity in the Taleshi dialect. This dialect is spoken in some parts of Guilan and appears in three main different types including Central, Northern, and Southern. The type of dialect surveyed in this article is the southern one. It is spoken in Sehsar village. The data are collected in a field study and by interviewing thirty native speakers of this dialect. Ergativity is a grammatical pattern in which the subject of an intransitive clause is treated in the same way as the object of a transitive clause, and differently from the transitive subject. This dialect follows a split-ergative system. This means that, in a present clause, it takes advantage of the nominative-accusative pattern, hence in a past transitive clause it takes advantage of the ergative-absolutive pattern. This research has been done to answer these questions: Is the ergative marker -i the only indicator of ergativity and ergative constructions in this dialect? Which constructions can be considered ergative ones? And on what factors is ergativity based on? After surveying language witnesses of this dialect, these findings have been achieved: Ergativity is not limited only to ergative marker -i , but oblique pronouns and plural nouns ending with -un in a transitive clause and past tense as well as perfect aspect can be the other indicators of ergative constructions. And finally, ergativity is based on past tense and perfect aspect.